Amplified Host Defense by Toll-Like Receptor-Mediated Downregulation of the Glucocorticoid-Induced Leucine Zipper (GILZ) in Macrophages - Hoppstädter, Jessica; Diesel, Britta; Linnenberger, Rebecca; Hachenthal, Nina; Flamini, Sara; Minet, Marie; Leidinger, Petra; Backes, Christina; Grässer, Friedrich; Meese, Eckart; Bruscoli, Stefano; Riccardi, Carlo; et al. (Frontiers in Immunology, 2019)
Activation of toll-like receptors (TLRs) plays a pivotal role in the host defense against bacteria and results in the activation of NF-B-mediated transcription of proinflammatory mediators. Glucocorticoid-induced leucine zipper (GILZ) is an anti-inflammatory mediator, which inhibits NF-B activity in macrophages. Thus, we aimed to investigate the regulation and role of GILZ expression in primary human and murine macrophages upon TLR activation. Treatment with TLR agonists, e.g., Pam3CSK4 (TLR1/2) or LPS (TLR4) rapidly decreased GILZ mRNA and protein levels. In consequence, GILZ downregulation led to enhanced induction of pro-inflammatory mediators, increased phagocytic activity, and a higher capacity to kill intracellular bacteria (Salmonella enterica serovar typhimurium), as shown in GILZ knockout macrophages. Treatment with the TLR3 ligand polyinosinic:polycytidylic acid (Poly(I:C)) did not affect GILZ mRNA levels, although GILZ protein expression was decreased. This effect was paralleled by sensitization towards TLR1/2- and TLR4-agonists. A bioinformatics approach implicated more than 250 miRNAs as potential GILZ regulators. Microarray analysis revealed that the expression of several potentially GILZ-targeting miRNAs was increased after Poly(I:C) treatment in primary human macrophages. We tested the ability of 11 of these miRNAs to target GILZ by luciferase reporter gene assays. Within this small set, four miRNAs (hsa-miR-34b*, -222, -320d, -484) were confirmed as GILZ regulators, suggesting that GILZ downregulation upon TLR3 activation is a consequence of the synergistic actions of multiple miRNAs. In summary, our data show that GILZ downregulation promotes macrophage activation. GILZ downregulation occurs both via MyD88-dependent and -independent mechanisms and can involve decreased mRNA or protein stability and an attenuated translation.